Pendekatan Cognitive Behavior Therapy (CBT) dalam Menangani Kepribadian Tidak Sehat melalui Koreksi Distorsi Kognitif - Khoerotun Nufus; Muhammad Robbi Alwalad; Mohammad Fariz Rizwan; Immalatul Khairat (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This article aims to theoretically examine the relationship between unhealthy personality, cognitive distortion, and the application of Cognitive Behavior Therapy (CBT) in counseling practice. This study uses a literature study method with a conceptual approach, namely analyzing relevant literature without collecting field data. The results of the study indicate that unhealthy personality is often influenced by cognitive distortions that cause individuals to view themselves and their environment negatively and irrationally. CBT is an effective counseling approach to help individuals recognize and reconstruct negative thought patterns to be more realistic and adaptive. In conclusion, CBT can be used as a psychological intervention strategy in dealing with unhealthy personality problems, especially in students who experience academic pressure and impostor syndrome.